SUBCONTINENT OF INDIA: A PART OF THE EARLIEST AND MOST ADVANCED CIVILISATION OF THE WORLD - Bhatt, Uditi (PEOPLE: International Journal of Social Sciences, 2019)
This paper examines the subcontinent of India from the point of view that it was partially home to the earliest and most advanced civilisation in the world. By examining this case, the paper clarifies the hold that the myths that have been around since centuries all over the world are not mere stories but in fact, they tell us a greater truth about the civilisation that existed at the end of the Ice Age. The topic studied in this paper includes the myths and folklores from around the world juxtaposed with each other in order to highlight the similarities. Each statement made in the paper is backed by scientific and archeological proof and thus the paper is divided into three major portions to prove the claim: (1) Mythical Parallels with History (2) Technological Brilliance in Ancient Scriptures (3) Archeological Proof. Data has been collected from documentary archives, interviews, books, newspaper archives, published reports and folklores. This paper challenges the argument that myths are inconsequential and are mere stories passed down since generations. It holds the view that a more technologically advanced civilisation existed before the time line that history gives us and if examined minutely, the proofs of its existence can be easily visible. This paper attempts to bring to light the existence of the mythical cities citied in ancient Indian texts and various other mythologies and how the Indian subcontinent was an integral part of it all.